Step
*
2
of Lemma
bag-summation-product
1. r : Rng
2. Assoc(|r|;+r)
3. Comm(|r|;+r)
4. A : Type
5. B : Type
6. f : A ⟶ |r|
7. c : bag(B)
8. g : B ⟶ |r|
9. u : A
10. v : A List
11. (Σ(x∈v). f[x] * Σ(y∈c). g[y]) = Σ(p∈v × c). f[fst(p)] * g[snd(p)] ∈ |r|
⊢ (Σ(x∈[u / v]). f[x] * Σ(y∈c). g[y]) = Σ(p∈[u / v] × c). f[fst(p)] * g[snd(p)] ∈ |r|
BY
{ Subst ⌜[u / v] ~ {u} + v⌝ 0⋅ }
1
.....equality..... 
1. r : Rng
2. Assoc(|r|;+r)
3. Comm(|r|;+r)
4. A : Type
5. B : Type
6. f : A ⟶ |r|
7. c : bag(B)
8. g : B ⟶ |r|
9. u : A
10. v : A List
11. (Σ(x∈v). f[x] * Σ(y∈c). g[y]) = Σ(p∈v × c). f[fst(p)] * g[snd(p)] ∈ |r|
⊢ [u / v] ~ {u} + v
2
1. r : Rng
2. Assoc(|r|;+r)
3. Comm(|r|;+r)
4. A : Type
5. B : Type
6. f : A ⟶ |r|
7. c : bag(B)
8. g : B ⟶ |r|
9. u : A
10. v : A List
11. (Σ(x∈v). f[x] * Σ(y∈c). g[y]) = Σ(p∈v × c). f[fst(p)] * g[snd(p)] ∈ |r|
⊢ (Σ(x∈{u} + v). f[x] * Σ(y∈c). g[y]) = Σ(p∈{u} + v × c). f[fst(p)] * g[snd(p)] ∈ |r|
Latex:
Latex:
1.  r  :  Rng
2.  Assoc(|r|;+r)
3.  Comm(|r|;+r)
4.  A  :  Type
5.  B  :  Type
6.  f  :  A  {}\mrightarrow{}  |r|
7.  c  :  bag(B)
8.  g  :  B  {}\mrightarrow{}  |r|
9.  u  :  A
10.  v  :  A  List
11.  (\mSigma{}(x\mmember{}v).  f[x]  *  \mSigma{}(y\mmember{}c).  g[y])  =  \mSigma{}(p\mmember{}v  \mtimes{}  c).  f[fst(p)]  *  g[snd(p)]
\mvdash{}  (\mSigma{}(x\mmember{}[u  /  v]).  f[x]  *  \mSigma{}(y\mmember{}c).  g[y])  =  \mSigma{}(p\mmember{}[u  /  v]  \mtimes{}  c).  f[fst(p)]  *  g[snd(p)]
By
Latex:
Subst  \mkleeneopen{}[u  /  v]  \msim{}  \{u\}  +  v\mkleeneclose{}  0\mcdot{}
Home
Index